1989
DOI: 10.1161/01.hyp.14.3.261
|View full text |Cite
|
Sign up to set email alerts
|

Atrial natriuretic factor in hypertension: bioactivity at normal plasma levels.

Abstract: To ascertain whether small shifts in plasma atrial natriuretic factor (ANF) exerted biological effects in hypertension, we studied the renal, hemodynamic, and hormonal effects of ANF ] infused at a dose (0.75 pmol/kg/min for 3 hours) that would induce changes in plasma ANF confined to the normal, resting range, in a group of six young men with uncomplicated, mild essential hypertension. During ANF infusions, the patients excreted 11.8±2.0 mmol (mean±SEM) sodium more than during the time-matched placebo phase n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
13
1

Year Published

1991
1991
1994
1994

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 32 publications
1
13
1
Order By: Relevance
“…The current data are derived from contrived circumstances in which plasma Ang II concentrations were rapidly elevated from normal to pathophysiological levels, and it remains to be confirmed that endopeptidase 24.11 inhibition will continue to significantly delay metabolic clearance of Ang II in the medium or longer term with more gradual or subtle elevation of endogenous angiotensin II, and, if so, whether such an action would be sufficient to exert significant hemodynamic effects. However, the potential importance of the observed interaction indicates that carefully controlled trials (of a range of endopeptidase inhibitors) that incorporate monitoring of both clinical status and neurohumoral status will be required to establish the appropriate role, if any, of endopeptidase 24.11 inhibitors in the management of cardiovascular disease.…”
mentioning
confidence: 97%
See 3 more Smart Citations
“…The current data are derived from contrived circumstances in which plasma Ang II concentrations were rapidly elevated from normal to pathophysiological levels, and it remains to be confirmed that endopeptidase 24.11 inhibition will continue to significantly delay metabolic clearance of Ang II in the medium or longer term with more gradual or subtle elevation of endogenous angiotensin II, and, if so, whether such an action would be sufficient to exert significant hemodynamic effects. However, the potential importance of the observed interaction indicates that carefully controlled trials (of a range of endopeptidase inhibitors) that incorporate monitoring of both clinical status and neurohumoral status will be required to establish the appropriate role, if any, of endopeptidase 24.11 inhibitors in the management of cardiovascular disease.…”
mentioning
confidence: 97%
“…'-4 Endopeptidase 24.11 appears to play a central role in the initial degradation of atrial natriuretic factor (ANF).5-7 Endopeptidase 24.11 inhibitors have been shown to enhance plasma ANF and induce ANF-like end-organ effects in animals as well as both normal volunteers and patients with hypertension and heart failure.2-4,8 ANF exerts beneficial hemodynamic effects in hypertension and heart failure,9'10 but data have been limited because of the peptide's short half-life and the necessity for parenteral administration. Therefore, orally active endopeptidase 24.11 inhibitors may offer a method for testing the effects of chronic enhancement of ANF bioactivity in cardiovascular disease.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…- 21 Of note is that the biologic response to an increase in plasma ANP levels after NEP inhibition is likely to be greater than after the same increase in plasma ANP after ANP infusion. This is because tissue levels of ANP at sites of ANP-guanylate cyclase receptor binding and NEP activity will be greater for the same plasma ANP level achieved after NEP inhibition compared with that after ANP infusion.…”
mentioning
confidence: 99%